2004
DOI: 10.1242/jcs.01142
|View full text |Cite
|
Sign up to set email alerts
|

Akt binds prohibitin 2 and relieves its repression of MyoD and muscle differentiation

Abstract: In a yeast two-hybrid screen using the full-length Akt as bait, we found that prohibitin 2 (PHB2) specifically interacts with Akt. The C terminus of Akt (amino acids 413-480) and a central region of PHB2 (amino acids 120-232) are responsible for their mutual interaction. PHB2 acts as a transcriptional repressor in cells. PHB2 interacts with both MyoD and MEF2, and represses both MyoD- and MEF2-dependent gene transcription. Furthermore, binding of PHB2 to both MyoD and MEF2 significantly decreases upon myogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
4
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 44 publications
3
98
4
1
Order By: Relevance
“…In the nucleus, PHB2 physically interacts with the estrogen receptor (43) and brefeldin A-inhibited guanine nucleotide-exchange protein 3 (BIG3) (44), resulting in suppression of gene transcription and contributing to tumor growth inhibition (10). In the cytosol, PHB2 but not PHB1 binds Akt2 and reciprocally regulates Akt2 levels and muscle differentiation (12,45). PHB2 also interacts with ␣-actinin and annexin A2 (46).…”
Section: Discussionmentioning
confidence: 99%
“…In the nucleus, PHB2 physically interacts with the estrogen receptor (43) and brefeldin A-inhibited guanine nucleotide-exchange protein 3 (BIG3) (44), resulting in suppression of gene transcription and contributing to tumor growth inhibition (10). In the cytosol, PHB2 but not PHB1 binds Akt2 and reciprocally regulates Akt2 levels and muscle differentiation (12,45). PHB2 also interacts with ␣-actinin and annexin A2 (46).…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt pathway has been shown to increase the transcriptional activity of MyoD (48 -50). Indeed, it has been demonstrated that activated Akt specifically interacts with prohibitine 2, competing with its binding to MyoD and thus increasing MyoD transcriptional activity (45). Inhibition of the PI3K/Akt pathway observed in Trpc1 Ϫ/Ϫ muscles could therefore explain the reduced level of myogenin and MHCd, the expression of which depends on MyoD.…”
Section: Discussionmentioning
confidence: 99%
“…However, the more interesting aspect concerns mesodermal commitment, as in the presence of matrigel engrafted 3AB-OS cells seemed to meet the appropriate environmental cues for committing along the mesenchymal lineage, with activation of myoblast differentiation. Differentiation of muscle progenitors is a multistep process that involves cell cycle withdrawal, expression of muscle-specific genes, and formation of multinucleated myofibers by cell fusion [Sun et al, 2004]. Moreover, it requires specific, but poorly understood, cell signals.…”
Section: Discussionmentioning
confidence: 99%